If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + (2 + -4x) = 4 Remove parenthesis around (2 + -4x) 3x + 2 + -4x = 4 Reorder the terms: 2 + 3x + -4x = 4 Combine like terms: 3x + -4x = -1x 2 + -1x = 4 Solving 2 + -1x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 4 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 4 + -2 -1x = 4 + -2 Combine like terms: 4 + -2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2
| 8/21k=1/3 | | y-aw=2w-1 | | 5-x/6=2x/3 | | -6y=-3x+18 | | X-3/5=2x/8 | | 4x/3=2/9 | | -9y+9x=18 | | 3x+5+2+4=19 | | 3(3.6x-5.4)-2.9x=-4(x-9.6) | | 123x+4= | | 0.2(4x-8.1)=2(3.2x-1.6) | | 8(x+2)=3y-x | | 3/(x^3-4x) | | 3.4(x-6)=-12.9 | | 2y+3x=-12 | | 2.3(x+3)=-9.66 | | 9a-54=0 | | ax-a(a+b)=-x-(-1+ab) | | (3p^-4)/(9p^7) | | 3-d+-2=4-2d+-4+7 | | 3/4(16x-8)=1/2(36x-7) | | 3/4(16x-8=1/2(36x-7) | | 5/6(2x-5)=1/3 | | 0.7x^2-0.7x+4.9=0.7 | | 4-6(2-8x)=3x+4(x-9) | | 3-(5x-4)=6+2(3x-1)+x | | cosx=8 | | -3(4x+2)-x=5(2-3x)+8 | | 4(2x-8)-3x=6(3-x)+9+2x | | 6-(-2d)=-6 | | -2(3x+5)=3(6-x) | | .2y-4=.5y-7 |